2015
DOI: 10.1371/journal.pone.0117156
|View full text |Cite
|
Sign up to set email alerts
|

F3MB(PANDER) Decreases Mice Hepatic Triglyceride and Is Associated with Decreased DGAT1 Expression

Abstract: ObjectivePancreatic-derived factor (PANDER, also named as FAM3B) is secreted by pancreatic α and β cells. Increasing evidence suggests that it may serve a hormonal function related to glycemic and lipid metabolism. In this study, we investigated the effects of PANDER overexpression on hepatic and adipose triglyceride metabolism in high-fat diet-fed male C57BL/6 mice.MethodsPANDER overexpression was achieved by tail-vein injection of recombinant Ad-PANDER and Ad-GFP injected mice served as a control. The TG met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…An elevation in circulating PANDER level is associated with insulin resistance and hyperglycemia in a Chinese population [ 29 ]. However, although liver-produced PANDER also plays important roles in regulating glucose and lipid metabolism, only one PANDER protein isoform (full length form, 27kD) can be detected in mouse livers and cultured hepatocytes with or without PANDER overexpression [ 9 , 10 , 13 , 30 ], suggesting that PANDER may not be processed and released from hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…An elevation in circulating PANDER level is associated with insulin resistance and hyperglycemia in a Chinese population [ 29 ]. However, although liver-produced PANDER also plays important roles in regulating glucose and lipid metabolism, only one PANDER protein isoform (full length form, 27kD) can be detected in mouse livers and cultured hepatocytes with or without PANDER overexpression [ 9 , 10 , 13 , 30 ], suggesting that PANDER may not be processed and released from hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Conditioned medium collected from hepatocytes with PANDER expression induces gluconeogenic gene expression and promotes gluconeogenesis in cultured hepatocytes [112]. However, secretory PANDER isoform cannot be detected in mouse livers and cultured hepatocytes with or without PANDER overexpression in several other reports [111,113,118]. These findings suggested that liver-derived PANDER likely promotes lipogenesis and gluconeogenesis via the intracellular and extracellular mechanisms.…”
Section: Liver-derived Pander In Glucose and Lipid Metabolismmentioning
confidence: 96%
“…This suggests that upregulation of PANDER is a novel mechanism for explaining the lipogenic and gluconeogenic effects of ChREBP [117]. However, one recent study reported that adenovirus-mediated overexpression of PANDER decreased TG content in normal mouse livers [118]. Although the reason for the discrepancy is not known, it is generally accepted that PANDER promotes gluconeogenesis and lipogenesis in the liver.…”
Section: Liver-derived Pander In Glucose and Lipid Metabolismmentioning
confidence: 99%
“…So far, whether or not PANDER can be released by other non‐islet cell types such as hepatocyte remains unclear. A putative secretory isoform of PANDER had been reported to be detected in the medium of cultured hepatocytes after PANDER overexpression, while the secretory PANDER isoform failed to be detected in mouse livers and cultured hepatocytes in several other studies . Moreover, a non‐secretory PANDER isoform has been reported to promote invasion and metastasis of human colon cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…A putative secretory isoform of PANDER had been reported to be detected in the medium of cultured hepatocytes after PANDER overexpression, 14 while the secretory PANDER isoform failed to be detected in mouse livers and cultured hepatocytes in several other studies. 13,21,22 Moreover, a non-secretory PANDER isoform has been reported to promote invasion and metastasis of human colon cancer cells. 23 Collectively, these findings had raised an important hypothesis that PANDER may modulate glucose and lipid metabolism via non-secretory mechanism in hepatocytes.…”
Section: Introductionmentioning
confidence: 99%